Factors Affecting Satisfaction Of The Surya Madina Umroh Pilgrimage - Sudino; Bambang Mursito; Sarsono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out the influence of service quality, price perception, customer trust, and promotions on customer satisfaction. Based on the objectives to be achieved, this research is categorized as quantitative descriptive research. This research was carried out at the research location at the Surya Madina Umrah Foundation. In this research, the objects of this research are Umrah customers at the Surya Madina Foundation. The planned time for research is January – December 2023. The population in this study is all 286 Surya Madina Surakarta Umrah pilgrims. The research took 50% of the population as a sample, namely 143 Surya Madina congregation members. The sampling technique in this research used random sampling. After obtaining sufficient data, the data was processed using multiple linear regression analysis tools which were processed using SPSS 26 software. The conclusions obtained were that service quality, price perception, customer trust and promotions had an influence on customer satisfaction.